Studi Eksplorasi Pengobatan Pada Usada Pemunah Cetik Kerikan Gangsa - Dwi Arymbhi Sanjaya; Asthadi Mahendra Bhandesa (Jurnal Penelitian Agama Hindu, 2019)
Lontar Usada Pemunah Cetik Kerikan Gangsa contains the Balinese poison, which containing the ingredients of poison, signs and symptomps of poison, and traditional therapy for poison. The Balinese community believed that the chronic illness may caused by cetik. Until now, there has been no evidence about Balinese poison and Balinese traditional therapy for poison. It is this which has inspired the researcher to explore the traditional therapy in usada pemunah cetik kerikan gangsa. This was an ecological study based on Lontar Usada Cetik Kerikan Gangsa and experience of traditional medicine practicioners in Denpasar area. This study was a descriptive qualitative research with in-depth interview method. We colected the information about usada pemunah cetik from traditional medicine practicioners in Denpasar area. The result showed that ingredients of cetik containing the heavy metal which high toxicity such as plumbum and copper. The traditional therapy for cetik kerikan gangsa using the lemon grass (Cymbopogon citratus) and coconut water (Cocos nucifera L).